Relevant Biological Effects of Varicocele Embolization with N-Butyl Cyanoacrylate Glue on Semen Parameters in Infertile Men - Olivier Chevallier; Patricia Fauque; Carole Poncelet; Kévin Guillen; Pierre-Olivier Comby; Karine Astruc; Julie Barberet; Nicolas Falvo; Emmanuel Simon; Romaric Loffroy (Biomedicines, 2021)
Surgical treatment or varicocele embolization (VE) with sclerosing or mechanical embolic agents have been shown to improve the semen parameters of infertile men. The aim of this study was to evaluate the impact of VE using N-butyl cyanoacrylate (NBCA) glue on semen parameters in infertile men. From January 2014 to June 2018, infertile adult patients with stage 3 varicocele and an initial semen analysis showing at least one abnormal semen parameter, and who were successfully embolized with NBCA Glubran®2 glue, were retrospectively recruited. The availability of a second semen analysis after VE was mandatory for patient inclusion. The primary endpoint was the change in total sperm number (TSN) after VE. The other parameters of interest were progressive and total sperm motilities (Smot) at 1 h (H1), sperm vitality (SV) and morphology (SMor). One hundred and two patients were included. Eight patients presented null TSN before and after VE. Among the remaining 94 patients, a significant improvement in the median TSN after VE was shown (31.79 × 106/ejaculate [IQR: 11.10–127.40 × 106/ejaculate] versus 62.24 × 106/ejaculate [IQR: 17.90–201.60 × 106/ejaculate], p = 0.0295). Significant improvement in TSN was found for the 60 oligo- or azoospermic patients (p = 0.0007), whereas no significant change was found for the 42 patients with normal initial TSN (p = 0.49). Other parameters, such as progressive and total SMot, SV and SMor, also significantly improved after VE (p = 0.0003, 0.0013, 0.0356 and 0.007, respectively). The use of NBCA glue as an embolic agent for VE in infertile men with stage 3 varicocele significantly improves the semen parameters.